FAUNISTIC ANALYSIS OF GROUND DIGGER WASPS OF (HYMENOPTERA: SPHECIDAE) FAMILY IN THE FERGANA VALLEY - Kadirov Ilhomjon Tajiakhmatovich (American Journals Publishing, 2025)
The article presents information about the location, distribution, bioecology of species Palmodes melanarius, Podalonia affinis, P.ebenina, Sceliphron madraspatanum F, Sphex funerarius.
Keywords: Hymenoptera, Apocrita, Apoidea, Sphecidae Sphex, genus, species.